Kebutuhan Perkembangan Siswa SD Islam Se-kota Kediri - Rahmawati, Novi Rosita; Laksana, Eko Pramudya; Kholidin, Farid Imam (citeus, 2025)
This study aims to determine the developmental needs of elementary school students throughout the city of Kediri. The instrument was distributed to 480 students from 12 schools in Kediri City. Based on the results of the analysis of the Inventori Kebutuhan Perkembangan Murid (IKPM) it was found that 311 students really needed the services of the teacher about learning to carry out Islamic religious orders/teachings sincerely. The second highest shows that students need services related to perseverance in worship in accordance with Islamic teachings. A total of 295 elementary school students in Kediri City also need services on how to understand the teacher's explanation. 278 requires a way to understand the teacher's instructions. A total of 263 voted in dire need of talent guidance. Teachers can provide guidance and counseling services according to student needs.